Centering Loss and Grief: Positioning Schools as Sites of Collective Healing in the Era of COVID-19 - Castrellón, Liliana E.; Fernández, Érica; Reyna Rivarola, Alonso R.; López, Gerardo R. (Frontiers in Education, 2021)
When the COVID-19 pandemic hit the United States, everyday life was fundamentally transformed. Schools and small businesses were forced to shut down. Individuals were encouraged to wear masks in public settings, "shelter-in-place" orders were implemented across several cities and states, and social distancing became a routine practice. Some lost their jobs and livelihood, while others lost the day-to-day physical connection with colleagues and friends, as their "work-life" shifted to the home. To be certain, the variety of losses that people individually and collectively experienced during the COVID-19 pandemic is quite vast—ranging from small, seemingly inconsequential losses (like the freedom to get a haircut) to more considerable and painful losses (like the loss of life). It is important to note that these losses overlapped with other crises that were fomenting across the nation at the same time—e.g., the rise of the white supremacist movement, Black Lives Matter, draconian immigration enforcement, amongst others. These other pandemics also produced losses such as the loss of civil rights, crackdowns on civic participation, and fundamental violations of basic human rights and civil liberties. In this paper, we discuss the "losses" we are currently experiencing as a nation and the need for school leaders to pay attention to the range of losses people are experiencing in their daily lives. We draw particular attention to those losses compounded by intersecting historical oppressions that disproportionately impact historically marginalized students, families, and communities. We also (re)imagine the transformation of schools to sites of collective healing that work to humanize the collective experience by anchoring actions in resistance, love, collective well-being, hope, and solidarity with and alongside teachers, students, families, and communities.